PENERAPAN MODEL PEMBELAJARAN COOPERATIF LEARNING TYPE MAKE A MATCH UNTUK MENINGKATKAN MOTIVASI DAN HASIL BELAJAR SISWA KELAS XI MIPA 1 MATERI SISTEM KOORDINASI DI SMAN 1 JATIBARANG - YUDA KUSDIAWATI (STRATEGY : Jurnal Inovasi Strategi dan Model Pembelajaran, 2022)
This study aims to increase learning motivation and student achievement by applying the cooperative model of the Make a Match method to the Coordination System material. From the results of direct observation of the research object in class XI MIPA 1 with a total of 36 students before the class action research was carried out, they had a relatively high heterogeneity of abilities. There is a low tendency to obtain daily test scores, and relatively low learning motivation. During the learning process, this class tends to be more crowded than other classes. Feedback from students when the learning process is also relatively passive and less active, besides that the supporting teacher is less varied when delivering teaching materials. The research process begins with preparing proposals, submitting permits, making instruments, collecting data, analyzing data, discussing and discussing and compiling research reports. After implementing the action through learning with the application of the Cooperative Learning type Make a Match learning model, the class atmosphere becomes alive, students become active in learning and have an impact on improving student learning outcomes. This research was carried out in 3 pre-cycle stages, Cycle I and Cycle II. The percentage of learning completeness in the pre-cycle stage was 45% while in Cycle I the percentage of student activity was 68.75% with an average score of 55. Meanwhile in cycle II there was an increase in student activity to 85.62% with an average score 89.12. From the implementation of cycles I and II there was an increase in student activity by 17.37% and an average increase in learning outcomes by 12.7%. This shows that the learning outcomes of students have met the targets set by the researcher. From the stages that have been carried out, it is evident that there has been an increase after applying the Cooperative Learning type Make a Match learning model with the previous one. ABSTRAKPenelitian ini bertujuan untuk meningkatkan motivasi belajar dan prestasi belajar siswa dengan penerapan model kooperatif metode Make a Match pada materi Sistem Koordinasi. Dari hasil pengamatan secara langsung pada obyek penelitian di kelas XI MIPA 1 dengan jumlah siswa 36 peserta didik sebelum dilakukan penelitian tindakan kelas memiliki heterogenitas kemampuan yang relative tinggi. Terdapat kecenderung yang masih rendah pada perolehan nilai ulangan hariannya, dan motivasi belajarnya relatif rendah. Ketika proses pembelajaran, kelas ini cenderung lebih ramai dibandingan kelas lainnya. Umpan balik dari peserta didik ketika proses pembelajaran juga relative pasif dan kurang aktif selain juga guru pengampu kurang bervariasi ketika menyampaikan materi bahan ajar. Proses Penelitian diawali dari penyusunan proposal, pengajuan ijin, pembuatan instrument, pengumpulan data, analisa data, pembahasan dan diskusi serta penyusunan laporan penelitian. Setelah dilaksanakan tindakan melalui pembelajaran dengan penerapan model pembelajaran Cooperatif Learning type Make a Match maka suasana kelas menjadi hidup, peserta didik menjadi aktif dalam belajar dan berdampak pada peningkatan hasil belajar peserta didik.Penelitian ini dilaksanakan dalam 3 tahap pra siklus, siklusI dan Siklus II. Prosentase ketuntasan belajar pada tahap pra siklus adalah 45 % sementara pada Siklus I prosentase keaktifan peserta didik adalah 68,75% dengan nilai rata-rata nilai 55. Sedangkan pada siklus II terjadi peningkatan aktifitas peserta didik menjadi 85,62% dengan nilai rata-rata 89,12.Dari pelaksanaan siklus I dan II terjadi peningkatan aktivitas peserta didik sebesar 17,37 % dan peningkatan rata-rata hasil belajar sebesar 12,7 %. Hal ini menunjukkan bahwa hasil belajar peserta didik sudah memenuhi target yang ditetapkan peneliti. Dari tahapan yang sudah dilakukan terbukti bahwa ada peningkatan sesudah diterapkan model pembelajaran Cooperatif Learning type Make a Match dengan sebelumnya.